Ligand-Specific Function of Transforming Growth Factor Beta in Epithelial-Mesenchymal Transition in Heart Development - Azhar, Mohamad (2009)
The ligand specificity of transforming growth factor beta (TGFβ) in vivo in mouse cardiac cushion epithelial-to-mesenchymal transition (EMT) is poorly understood. To elucidate the function of TGFβ in cushion EMT, we analyzed Tgfb1 (−/−), Tgfb2(−/−) and Tgfb3(−/−) mice between embryonic day (E) 9.5 and E14.5 using both in vitro and in vivo approaches. Atrioventricular (AV) canal collagen gel assays at E9.5 indicated normal EMT in both Tgfb1(−/−) and Tgfb3(−/−) mice. However, analysis of Tgfb2(−/−) AV explants at E9.5 and E10.5 indicated that EMT, but not cushion cell proliferation, was initially delayed but later remained persistent. This was concordant with the observation that Tgfb2(−/−) embryos, and not Tgfb1(−/−) or Tgfb3(−/−) embryos, develop enlarged cushions at E14.5 with elevated levels of well validated indicators of EMT. Collectively, these data indicate that TGFβ2, and not TGFβ1 or TGFβ3, mediates cardiac cushion EMT by promoting both the initiation and cessation of EMT.